High-Resolution HLA Typing of HLA-A, -B, -C, -DRB1, and -DQB1 in Kinh Vietnamese by Using Next-Generation Sequencing - Do, Minh Duc; Le, Linh Gia Hoang; Nguyen, Vinh The; Dang, Tran Ngoc; Nguyen, Nghia Hoai; Vu, Hoang Anh; Mai, Thao Phuong (Frontiers in Genetics, 2020)
Human leukocyte antigen (HLA) genotyping displays the particular characteristics of HLA alleles and haplotype frequencies in each population. Although it is considered the current gold standard for HLA typing, high-resolution sequence-based HLA typing is currently unavailable in Kinh Vietnamese populations. In this study, high-resolution sequence-based HLA typing (3-field) was performed using an amplicon-based next-generation sequencing platform to identify the HLA-A, -B, -C, -DRB1, and -DQB1 alleles of 101 unrelated healthy Kinh Vietnamese individuals from southern Vietnam. A total of 28 HLA-A, 41 HLA-B, 21 HLA-C, 26 HLA-DRB1, and 25 HLA-DQB1 alleles were identified. The most frequently occurring HLA alleles were A*11:01:01, B*15:02:01, C*07:02:01, DRB1*12:02:01, and DQB1*03:01:01. Haplotype calculation showed that A*29:01:01 B*07:05:01, DRB1*12:02:01 DQB1*3:01:01, A*29:01:01 C*15:05:02 B*07:05:01, A*33:03:01 B*58:01:01 DRB1*03:01:01, and A*29:01:01 C*15:05:02 B*07:05:01 DRB1*10:01:01 DQB1*05:01:01 were the most common haplotypes in the southern Kinh Vietnamese population. Allele distribution and haplotype analyses demonstrated that the Vietnamese population shares HLA features with South East Asians, but retains unique characteristics. Data from this study will be potentially applicable in medicine and anthropology.